PENGGUNAAN MODEL SNOWBALL THROWING TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA TUNARUNGU KELAS V DI SDLB-B - SILVI ANJELIA HARAHAP, RIFKA (Jurnal Pendidikan Khusus, 2017)
ABSTRACT Hearing impairment students experienced disturbance to their hearing. As a consequence they were difficult to master language and low vocabulary. One of the aspects which should be obtained by the hearing impairment children was reading comprehension ability. The purpose of this research was to know whether there was influence of using snowball throwing method toward reading comprehension ability to hearing impairment students of class V in SDLB-B Karya Mulia I Surabaya or not. The research kind used was pre experiment using “one group pre-test post-test design”. The subjects in this research were hearing impairment students of class V numbering 7 students. The data collection technique used test. The technique of data analysis used statistic non parametric wilcoxon match pair test. The result of data analysis indicated that the average value of pretest was 43,21 and the average value of posttest was 88,56 so it produced Z counted 2,52 greater than Z table with critic value 5% i.e. 1,96. So, it was obtained that the usage of snowball throwing method significantly influenced toward reading comprehension ability to hearing impairment students of class V in SDLB-B Karya Mulia I Surabaya.   Keywords: reading comprehension, snowball throwing